2013
DOI: 10.5194/acp-13-6227-2013
|View full text |Cite
|
Sign up to set email alerts
|

An examination of parameterizations for the CCN number concentration based on in situ measurements of aerosol activation properties in the North China Plain

Abstract: Precise quantification of the cloud condensation nuclei (CCN) number concentration is crucial for understanding aerosol indirect effects and characterizing these effects in models. An evaluation of various methods for CCN parameterization was carried out in this paper based on in situ measurements of aerosol activation properties within HaChi (Haze in China) project. Comparisons were made by closure studies between methods using CCN spectra, bulk activation ratios, cut-off diameters and size-resolved activatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 57 publications
1
54
1
1
Order By: Relevance
“…Many studies have used CCN counters to investigate the critical supersaturation of ambient aerosol particles as well as the CCN number concentration under controlled supersaturation conditions (e.g. Fors et al, 2011;Padro et al, 2012;Deng et al, 2013;Sihto et al, 2011).…”
Section: E Hammer Et Al: Cloud Activation Behaviour At a High-alpinmentioning
confidence: 99%
“…Many studies have used CCN counters to investigate the critical supersaturation of ambient aerosol particles as well as the CCN number concentration under controlled supersaturation conditions (e.g. Fors et al, 2011;Padro et al, 2012;Deng et al, 2013;Sihto et al, 2011).…”
Section: E Hammer Et Al: Cloud Activation Behaviour At a High-alpinmentioning
confidence: 99%
“…Studies have addressed the relative importance of the size distribution, particle composition, and mixing state in determining CCN activation, but there are disagreements on the relative importance of these parameters (e.g., Roberts et al, 2002;Feingold, 2003;Ervens et al, 2005;Mircea et al, 2005;Dusek et al, 2006a;Anttila and Kerminen, 2007;Hudson, 2007;Quinn et al, 2008;Zhang et al, 2008;Deng et al, 2013. CCN closure studies are a useful approach to test our knowledge of the controlling physical and chemical factors and to help verify experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CCN measurements have been collected during field campaigns carried out in the region (Wiedensohler et al, 2009;Gunthe et al, 2011;Yue et al, 2011;Deng et al, 2011Deng et al, , 2013Zhang et al, 2014). These studies have presented different perspectives on the influence of particle size and composition on CCN activity.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have presented different perspectives on the influence of particle size and composition on CCN activity. For example, Deng et al (2013) evaluated various schemes for CCN parameterization and recommended that the particle number size distribution (PSD) together with inferred mean size-resolved activation ratios can be used to estimate CCN number concentrations without considering the impact of particle composition. However, Zhang et al (2014) demonstrated that the 30-40 % uncertainties in N CCN are mainly associated with changes in particle composition.…”
Section: Introductionmentioning
confidence: 99%